2009
DOI: 10.3144/expresspolymlett.2009.98
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-oxidative degradation of graphite/epoxy composite laminates: Modeling and long-term predictions

Abstract: Abstract. Thermo-oxidative degradation of graphite/epoxy composite laminates due to exposure to elevated temperatures was characterized using weight loss and short beam strength (SBS) reduction data. Test specimens obtained from 24-ply, unidirectional AS4/3501-6 graphite/epoxy laminates were subjected to 100, 150, 175, and 200°C for 5000 hours (208 days) in air. Predictive differential models for the weight loss and short beam strength reduction were developed using the isothermal degradation data only up to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The weight loss rises sharply during the initial 100 h of aging. This may be attributed to desorption of the residual moisture and volatiles and is not related to polymer degradation [27,87]. A faster weight loss rate is evident over the 400 to 600 h range.…”
Section: Weight Loss Measurementsmentioning
confidence: 90%
See 1 more Smart Citation
“…The weight loss rises sharply during the initial 100 h of aging. This may be attributed to desorption of the residual moisture and volatiles and is not related to polymer degradation [27,87]. A faster weight loss rate is evident over the 400 to 600 h range.…”
Section: Weight Loss Measurementsmentioning
confidence: 90%
“…Thermal-oxidative aging may irreversibly change the chemical structure of polymer matrix composites [13,14]. Alterations to the chemical structure during thermooxidative [1,9,13,[15][16][17][18][19][20][21][22], loss of volatiles [2,[23][24][25][26][27], dehydration [13,28,29], chain scission [25,[30][31][32][33][34], additional cross-linking [1,13], and carbonyl growth [19,29]. The initial chemical changes are accompanied by dehydration of secondary alcohols and the release of low molecular weight gaseous species due to random chain scission.…”
Section: Introductionmentioning
confidence: 99%
“…The initial weight loss may be attributed to the desorption of the residual moisture and volatiles and may not be attributed to polymer degradation. 40 The epoxy composites with –NH 2 and –COOH functionalized MWCNTs showed slightly more mass and thickness changes at longer exposure periods, which appears related to polymer chain scission. The spray-washing used to simulate rain during the aging of epoxy and epoxy-composites may have caused some mass loss, where the wet aging process further oxidized and weakened the surface of the aged samples and led to the loss of microplastic fragments and nanofibers from the samples during aging.…”
Section: Results and Data Analysismentioning
confidence: 92%
“…A rapid preliminary of weight loss up to 336 h aging on the curves obtained from both neat and nano-filled GE specimens may be attributed to degassing and/or desorption of moisture and volatiles during high-temperature exposure. 21,37 Then, from around 336 h, the mass of the thermally aged GE specimens decreased with a lower rate and gradually moved toward stability.
Figure 4.Weight loss rate for (a) FML and, (b) GE specimens versus aging time at 130 ℃.
…”
Section: Resultsmentioning
confidence: 99%
“…Ozcelik et al. 21 reported that the thermo-oxidative aging has a significant effect on weight loss and mechanical properties of graphite/epoxy composites. After 5000 h of thermo-oxidative aging at 150 ℃, 175 ℃, and 200 ℃, respectively, 0.81, 2.31, and 5.84% weight loss associated with 10.87, 33.07, and 49.86% short beam strength reduction were observed.…”
Section: Introductionmentioning
confidence: 99%